Optimization of the operating parameters of membrane bio-reactor - Wee, Tio (2017)
The application nanofiber flat sheet membrane for wastewater treatment is relatively new. Flat sheet nanofibers possess larger surface area to volume ratio provides the opportunity of increasing water permeation. The understanding on its potential applicability remains unanswered. Hence, this study intends to focus on the feasibility of using the flat sheet nanofiber membrane in a closed looped membrane bioreactor set up treating sewage. In this study, a closed looped membrane bioreactor system to treat synthetic wastewater was designed, set-up and operated with the nanofiber flat sheet membrane for 152 days. This was to assess its feasibility as new generation membrane which could replace the current membrane technology. The study was divided into three phase. The set-up phase, to set up the physical structure of membrane bioreactor and ensure the structural and hydraulic integrity of the system. Follow by, the start-up phase to provide conditions for the flourishment of the microbial community in the membrane bioreactor system. Lastly, the optimization phase to study the feasibility of running the membrane bioreactor with high flux output while maintaining the intended treatment objective. The removal efficiencies of the membrane bioreactor in terms of Biochemical Oxygen Demand, Chemical Oxygen Demand and Total Organic Carbon were studied with varying the operating conditions such as hydraulic retention time and solid retention time. The membrane bioreactor could produce a stable flux of 33 litres per square meter per hour while delivering its intended treatment objective. It was found that the membrane bioreactor could remove 99.55% of Biochemical Oxygen Demand, 97.70% of Chemical Oxygen Demand and 97.75% of Total Organic Carbon from the synthetic wastewater source.